Utilization of redox and aggregation properties of methylene blue dye in nanobiophysical investigations - Шелковский, В. С. (Biophysical Bulletin)
Novel potentialities of applications of popular cationic dye Methylene Blue in molecular biophysical investigations and nanotechnology are considered in this review. The main attention is paid to utilization of redox and aggregation properties of Methylene Blue in modeling of biophysical processes and elaboration of schemes for nanodevices functioning at the molecular level. Approaches to study of methylene blue-involving redox processes and its interactions with nanomaterials using possibilities of experimental mass spectrometric techniques are systematized.